Burbujas en el precio del petróleo a causa de especulación e intereses políticos en el siglo XXI (2017)
"This study uses econometric bubble detection tests on the price of a barrel of WTI crude oil. It was detected using the recursive methodology of Phillips and Yu (2015) finding a negative bubble in the years 2015 and 2016. Using the quotient between the monthly nominal price of the WTI and the monthly China Production Index as the fundamental price. It was also found that the peaks in oil prices in 2014 and 2008 were explosive type and were determined by noise traders and political interests between superpowers and large oil producers." -- Tomado del Formato de Documento de Grado.